Whole Transcriptome Analyses Reveal Differential mRNA and microRNA Expression Profiles in Primary Human Dermal Fibroblasts Infected with Clinical or Vaccine Strains of Varicella Zoster Virus - Soo-Jin Oh; Sooyeon Lim; Moon Jung Song; Jin Hyun Ahn; Chan Hee Lee; Ok Sarah Shin (Pathogens, 2019)
Licensed live attenuated vaccines have been developed to prevent varicella zoster virus (VZV) infection, which causes chickenpox and shingles. The genomic sequences of both clinical- and vaccine-derived VZV strains have been analyzed previously. To further characterize the molecular signatures and complexity of wildtype (clinical) versus attenuated (vaccine-derived) VZV-mediated host cellular responses, we performed high-throughput next generation sequencing to quantify and compare the expression patterns of mRNAs and microRNAs (miRNAs) in primary human dermal fibroblasts (HDFs) infected with wildtype (YC01 low passage) and attenuated (YC01 high passage, SuduVax, and VarilRix) VZV strains. 3D-multidimensional scaling of the differentially expressed genes demonstrated the distinct grouping of wildtype and attenuated strains. In particular, we observed that HDFs infected with attenuated strains had more differentially expressed genes (DEGs) involved in the retinoic-acid inducible gene−I-like receptor and interferon-mediated signaling pathways compared with wildtype strains. Additionally, miRNA expression patterns were profiled following the infection of HDFs with VZV. Small RNA sequencing identified that several miRNAs were upregulated, including miR-146a-5p, which has been associated with other herpesvirus infections, whereas let-7a-3p was downregulated in both wildtype and attenuated VZV-infected cells. This study identified genes and miRNAs that may be essential in VZV pathogenesis.